Establishment of Babesia laboratory model and its experimental application - Jalovecká, Marie (Jihočeská univerzita, 2017)
Growing incidence of infections caused by the tick-transmitted protozoan parasite Babesia spp. defines babesiosis as an emerging disease from the aspect of human and veterinary medicine. The thesis provides an insight to biology of two main agents of human babesiosis, Babesia microti and Babesia divergens. We introduce here the fully optimized quantification model of Babesia parasite enabling the detailed investigation of the parasite developmental cycle and identification of molecules playing a role in its acquisition and transmission by the vector Ixodes ricinus. Novel and detailed information about Babesia dissemination within the tick tissues are given by newly implemented visualization and quantification techniques. Special emphasis is paid to parasite development in the tick salivary glands, the primary site responsible for parasite transmission from the vector into the host. Using gene-specific silencing we screene the tick immune pathways including effector molecules and evaluate their role in Babesia acquisition. We also provide a detailed view to Babesia parasite sexual commitment by monitoring its kinetics upon various stimuli. Moreover, a new direction of anti-babesial therapy is proposed by validation of the Babesia proteasome as a drug target. Overall, the research presented in the thesis extends the current knowledge of the Babesia parasite biology including molecular interactions at the tick-Babesia interface and thereby could significantly contribute to a potential control of babesiosis.
Establishment of Babesia laboratory model and its experimental application
Keywords: Babesia divergens; Babesia microti; transmission model; tick; immune interactions; signalling pathways; sexual commitment; proteasome; Babesia divergens; Babesia microti; transmission model; tick; immune interactions; signalling pathways; sexual commitment; proteasome